An extended goal programming methodology for analysis of a network encompassing multiple objectives and stakeholders - Jones, Dylan; Florentino, Helenice [UNESP]; Cantane, Daniela [UNESP]; Oliveira, Rogerio [UNESP] (Elsevier, 2016)
This paper proposes a goal programming methodology to ensure that a mix of balance and optimisation is achieved across a hierarchical decision network. The extended goal programming principle is used for this purpose. A model is constructed that provides consideration of balance and efficiency of multiple objectives and stakeholders at each network node level. A goal programming formulation to provide the decision that best meets the goals of the network is given. The proposed model is controlled by three key parameters that represent the level of non-compensation between objectives, level of non-compensation between stakeholders, and level of centralisation in the network. The methodology is demonstrated on an example pertaining to regional renewable energy generation and the results are discussed. Conclusions are drawn as to the effect of different attitudes towards compensatory behaviour between objectives and stakeholders in the network.
Keywords: Extended goal programming; Multiple objective programming; Renewable energy